Human Rights: From Theory to Politics - A. I. Kugay (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The article addresses human rights from the perspectives of defining their conceptual foundations, considering them as an element of geopolitics and a context-oriented approach to ensuring them. The recognition of the dignity of the human person — the main thing, on what is based the concept of human rights. The idea of human dignity manifests itself in the equal status of each person and is expressed in the fact that at birth each person becomes a member of the corporate body of humanity. From this point of view, any attempt to deprive a person of his “innate” corporate identity as a member of humanity is precisely what constitutes a violation of human rights. At the same time, practice should be separated from rhetoric. At the level of political practice, the history of human rights, as in the time of Locke, retains all the signs of social inequality, remains the history of drawing the boundaries of the rights of some social groups, strata and peoples at the expense of limiting others. Identifying the essence of human rights with Western culture denies the possibility for other cultures to have the same rights. Affirming that those who are not part of Western culture are excluded from the human rights radar. Accordingly, the most productive approach in the theory and practice of ensuring human rights is the context-oriented approach, which involves representatives of different cultures in the dialogue, who do not necessarily share the same understanding of human rights ethics, acting as a context-dependent universality.